Analisis Fundamental dan Teknikal Saham PT. Bank BTPN Syariah Tbk - Meidya Putri; Husni Shabri (Al-bank: Journal of Islamic Banking and Finance, 2022)
The purpose of this study is to determine whether the company's fundamental performance is in line with stock price movements in the Capital Market. The research was conducted using a qualitative descriptive method. The analysis technique is fundamental analysis and technical analysis of PT. Bank BTPN Syariah Tbk. The data used are financial reports and stock trading statistics obtained from the Indonesia Stock Exchange. The results showed that the fundamental performance since 2015-2019 as measured by EPS, ROE, ROE and PER showed very good growth. Meanwhile, along with the ongoing pandemic in 2020, there was a decline in fundamental performance with indicators of EPS, ROE, ROA dropping significantly. Meanwhile, in terms of technical analysis, it is in line with the company's performance. Where from 2018 to 2019 the stock price experienced an uptrend (increase) phase and PER was at 14-15x, which means the stock price was considered cheap (undervalued). Meanwhile in 2020, along with the decline in fundamental performance, the movement of BTPS stock prices experienced a downtrend phase with stock valuations being quite expensive (overvalued) at 43x.